Mycorrhiza Diversity in Some Intercropping Systems of Potato (Solanum tuberosum L) and Faba Bean (Vicia faba L) - Adventio Purnamadya Taurinanda; Dina Rotua Valentina Banjarnahor (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Arbuscular mycorrhizal fungi (AMF) is the most widely distributed mycorrhizal fungi in the soil and can make a symbiosis with the roots of host plants to form arbuscular mycorrhizal symbionts. Intercropping is a practice of polyculture cropping where two or more plant species are simultaneously cultivated in the same field. The objective of this study was to define the effect of intercropping on the density and diversity of mycorrhizal spores. In this study, potatoes and faba beans, both of which have the ability to symbiosis with mycorrhizae, were intercropped. A randomized group design with 5 planting system treatments was employed in this study with 5 replications. The results concluded that density of mycorrhizal spores in the intercropping planting pattern was not statistically different from the density of mycorrhiza in the monoculture cultivation pattern. The types of mycorrhiza found included the genus of Glomus, Funneliformis, Scutellospora, Cetraspora, Septoglomus, and Entrophospora Keywords: pH; Root exudate; Spore density, Spore identification; Spore diversity.